Participation and the Person in Pauline Theology: A Response to Susan Eastman's Paul and the Person. (June 2018) - Linebaugh, Jonathan A.
Paul and the Person by Susan Eastman both models a form of boundary-crossing Pauline scholarship and proposes a 'contemporary expression' of Paul's language of participation in Christ. In conversation with ancient and contemporary theories of the self, Eastman argues that, for Paul, the person is constituted in relationship, whether to sin or to Christ. This thesis is both significant and suggestive, but it does raise questions about the continuity of the person in Pauline theology.